Straightforward Three-Component Synthesis of N′,N′′-Disubstituted N-Alkyl-1,3,5-Triazinanes - Kletskov, Alexey V.; Frontera, Antonio; Sinelshchikova, Anna A.; Grigoriev, Mikhail S.; Zaytsev, Vladimir P.; Grudova, Mariya V.; Bunev, Alexander S.; Presnukhina, Sofia; Shetnev, Anton; Zubkov, Fedor I. (Synlett, 2020)
Efficient approaches towards the synthesis of various N-substituted 1,3,5-triazinanes based on a transformation of N-alkyl-1,5,3-dioxazepanes or on a domino reaction involving condensation of various amines, amides, and paraformaldehyde are described for the first time. Mg(ClO4)2 was shown to be one of the most potent additives for the condensation. The proposed approaches permit the synthesis of a broad spectrum of substituted sym-triazinanes in good yields with relatively easy workup. In the case of the multicomponent reaction, the approach allows the preparation of the target substances from simple and easily accessible reagents. The representatives of the resulting compounds were found to possess no antimicrobial or cytotoxic activity in in vitro bioassays.
Keywords: triazinanes; domino reaction; sulfonamides; amides; amines; thiourea